PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR TERHADAP PENGUASAAN KONSEP DAN BERPIKIR KREATIF PADA PEMBELAJARAN TEMATIK INTEGRATIF SISWA KELAS IV SD KABUPATEN SIKKA - Athanasia Dian Setiati; Devi Anggi Friani; Erlina Yuliastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigated the effect of using the surrounding environment as a learning resource on concept mastery and creative thinking among fourth-grade students in Sikka Regency. A quasi-experimental design with a pretest-posttest control group was applied. The population included all fourth-grade students in the area, with SDK Maumere I serving as the control group receiving traditional teacher-centered instruction, and SDK Maumere III as the experimental group using the environment as a learning resource. Samples were selected through simple random sampling. Research instruments included tests measuring creative thinking and concept mastery. Data were analyzed for homogeneity using Box’s M test and for normality using the Kolmogorov-Smirnov method. Hypotheses were tested using independent sample t-tests for univariate mean differences and MANOVA with Hotelling T² for multivariate effects. Results indicated that environmental-based learning significantly improved concept mastery (p = 0.000), enhanced creative thinking (p = 0.037), and positively affected both outcomes simultaneously (p = 0.000). The findings suggest that integrating the environment into thematic learning can effectively promote both conceptual understanding and creative skills in elementary students.